2018
DOI: 10.1192/bja.2018.46
|View full text |Cite
|
Sign up to set email alerts
|

Tardive dyskinesia update: treatment and management

Abstract: SUMMARYThe development of rational treatments for tardive dyskinesia has been held back by limitations to our understanding of its aetiology, which even now does not extend far beyond its association with centrally acting dopamine-blocking drugs. This article reviews briefly the major aetiological theories and addresses general management and specific treatment options. Primary prevention and early recognition remain the crucial management issues because, once the condition is established, there are no satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“…There is no satisfactory treatment for TD, emphasising the importance of primary prevention. Attempts to modify antipsychotic regimens may be tried, but any changes of type of medication (reducing potency) and/or dose should be undertaken very gradually, over weeks or months, to minimise the risk of withdrawal-emergent exacerbation of disorder which may not entirely resolve (Owens, 2019b). Support for the most advocated treatments springs from small, underpowered studies (Bergman et al, 2017) that, in addition, do not separate out movement types and/or distributions which may respond differentially, or allow for confounding by non-specific (e.g.…”
Section: Tardive Dyskinesiamentioning
confidence: 99%
See 4 more Smart Citations
“…There is no satisfactory treatment for TD, emphasising the importance of primary prevention. Attempts to modify antipsychotic regimens may be tried, but any changes of type of medication (reducing potency) and/or dose should be undertaken very gradually, over weeks or months, to minimise the risk of withdrawal-emergent exacerbation of disorder which may not entirely resolve (Owens, 2019b). Support for the most advocated treatments springs from small, underpowered studies (Bergman et al, 2017) that, in addition, do not separate out movement types and/or distributions which may respond differentially, or allow for confounding by non-specific (e.g.…”
Section: Tardive Dyskinesiamentioning
confidence: 99%
“…Good quality, independent studies conducted in the 1980s and 1990s reported a prevalence of 20% in younger populations with schizophrenia (Muscettola et al, 1993; Woerner et al, 1991), though this figure is inflated substantially (>50%) with the inclusion of mild abnormality (Owens, 2019b). An annual incidence of 5% was found (Chakos et al, 1996; Morgenstern and Glazer, 1993), which increases by some five to sixfold when first exposure is after middle life (Jeste et al, 1995).…”
Section: Extrapyramidal Side Effectsmentioning
confidence: 99%
See 3 more Smart Citations